Dual microring resonators for polymeric waveguide optical biosensors fabrication - Mohd Salleh, Mohd Hazimin; Mohd Salleh, Mohd Haziq; Abdul Hadi, Muhammad Salihi (2016)
In this work, we demonstrate the potential of fabricated dual microring resonator polymer waveguide as an optical biosensor. Visible wavelength region at 632 nm is used as a centre wavelength because it is commonly used in biological and chemical sensing for both label and label-free sensing. The double microring resonator waveguide structure is simulated using COMSOL Multiphysics optical design and analysis software. The results show that there is a transmission drop with a 3 dB bandwidth of 631.4 nm when the surrounding refractive index is 1.33. The specific wavelength (output transmission) is shifted to 674.6 nm when we increased the surrounding medium into 1.43 to imitate the bioanalytes solution. According to simulation result, the wavelength shift was approximately 43.2 nm for 0.1 increasing of surrounding refractive index. The dual microring resonator polymer waveguide was fabricated by using electron beam lithography. Then, the fabricated devices were integrated into microfluidic systems in order to validate the wavelength shift. From the experiments, the wavelength shift occurred approximately 22.3 nm over 0.1 increment of refractive index. Thus both simulation and experimental results strongly indicate that dual microring resonator polymer waveguide structure at visible wavelength region have a potential for label or label-free optical biosensing applications.